Disaster contingency recovery planning (DCRP): Management role - Ku Bahador, Ku Maisurah; Danila, Raudah (2005)
This paper presents an analysis of selected MSC companies in a survey of Disaster Contingency Recovery Planning (DCRP). In particular, it examines the role of management in planning and setting priorities for contingency planning, especially in those organizations that have specified IT is vertical to business operations. At present, the level of adoption of DCRP in Malaysia is moderate. Only 40.4% of the companies are currently implementing the DCRP plan. However, it is believed that there would be a rapid development in DCRP in future based on the fact that the respondents perceived the benefits outweigh the barriers.